Stunting prevalence and its associated factors among children in primary school in Sidoarjo District: A secondary data analysis - Lini Anisfatus Sholihah (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
Stunting is one under-nutrition condition that might be caused by inadequate nutrition consumption or frequent infection. Stunting prevalence in primary school-age children (PSAC) is still high in the third world and Indonesia. This present paper aimed to study the prevalence and the associated factors such as sex, school-area, and food intakes of stunting in PSAC in Sidoarjo, 2018. This study is cross-sectional research using secondary data from baseline data of emotional demonstration projects in primary school students. Two hundred students were recruited from four schools representing urban and rural areas in Sidoarjo. Food intake was interviewed using SQ-FFQ. Children height was measured using microtoice. HAZ-score was calculated using WHO Anthro Plus software. Student t-test was done to test any differences in stunting prevalence between sex and school areas. The Chi-square test was used to check the difference in proportion for categories. Our results suggested the stunting prevalence among PSAC in Sidoarjo was 18% and was significantly greater in the rural area (p= 0,010). School location has association with stunting (OR= 2,7; 95%CI 1,25-5,8). In conclusion, we did not find any significant difference in food intakes, although stunted children were more likely to consume energy and carbohydrate. This condition must be considered to prevent obesity in stunted children